MODEL KOMUNIKASI INTERNASIONAL PERJANJIAN HUDAIBIYAH SEBAGAI METODE DAKWAH ERA MASYARAKAT EKONOMI ASEAN (MEA) - Sudir Koadhi; Moh Natsir Mahmud; Muliaty Amin (TASÂMUH, 2018)
The discourse of the da’wah method in the framework of Southeast Asian regionalism is a matter purely in contact with the reasoning of mad'u life, the fulfilment of the essential elements of life (zimam al-hayah). Context restores the idea of Muslims passing into the era of the ASEAN Economic Community (MEA) which began to be applied gradually since 2015 with the motto of one vision, one identity and one community, becoming the embryo of the construction of Hudaibiyah international communication model for the first time. The main idea of the construction of the international communication model of this Hudaibiyah Treaty which is a representation of the necessity of syumuliyyat al-Islam is wus'ah maidan al-da'wah (an expanding dakwah field). The construction of the international communication model The Hudaibiyah Treaty is very relevant to be put forward as the primary tool in formulating the method of da'wa era of the MEA